Penerapan metode Missouri Mathematics Project (MMP) untuk penguasaan persamaan dan pertidaksamaan kuadrat satu variabel - Etty Soelistyowati Wulandari (LPMP Provinsi DKI Jakarta, 2021)
The ability to master the material quadratic equations and inequatnies one variable in mathematics learning in SMK is a pivotal important, This notion is based on a foundation in learning mathematics with a higher level and according to KKM. The problem in this study is whether the application of the Missouri Mathematical Project (MMP) learning model can improve students' mastery in mathematics. The number of participant in this study was 32. The sample was taken by random sampling method. Data collection uses written test of mathematics mastery and non-test, that was, observation and questionnaires. The data analysis procedure uses simple statistics with the help of an excel application. The study has come up with the following results in the first cycle the average score was 73 in the second cycle to an average score of 79. From the results of the study, it can be concluded that overall the MMP learning method can enhance students' mastery.